KINERJA KOMISI PEMILIHAN UMUM (KPU) KOTA PALU DALAM PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN RI TAHUN 2009 DI KOTA PALU - Irwan Waris (Indonesian Journal of Dialectics, 2011)
This study aims to answer the research question: how the performance of Palu City Commission in the implementation of the General Election of President and Vice President in 2009. To answer that question with research conducted using qualitative research methods with the approach of phenomenology. This approach reflects the direct experience of man, as far as the experience was intensely associated with an object. Moreover this approach also seeks to understand how a person experiences and give meaning to an experience. As a qualitative approach, the main instrument of this study is the researchers themselves. The source data of this study, is the city of Palu KPU officials and their staffs, the voting public, and other stakeholders. Data collection techniques used, is in-depth interviews, library study, and study the document.This study concluded that the Commission's performance in implementing PPWP Palu in 2009 in Palu achievements have not been satisfactory, due not only because it is less based on performance aspects, namely: output, effieciency, productivity, service quality, effectiveness, cost-effectiveness, and customer satisfaction,  but also because of the neglect of aspects of organizational commitment as a condition for the achievement of every aspect of performance.New concept are the findings of this study, the achievement of organizational commitment  condition of every aspect of performance. This new concept complements the concept of performance in public administration, especially those conceived by Poister (2003).